“I hope I get it. I do hope I figure it out.”: pre-service secondary language arts teachers’ negotiations of high school students’ literacies - Skillen, Matthew Glen (Kansas State University, 2009)
As the curriculum of American schools becomes more standardized, while teachers face the elevated levels of accountability, and definition of adolescent literacy rapidly expands, teacher education programs must do more to help pre-service teachers prepare for the realities of public education (Boyd, Ariail, Williams, Jocson, & Sachs, 2006). Among these realities exists the looming pressure to demonstrate the ability to help students succeed on standardized assessments that test comprehension-based literacy skills. Meyer (1999) suggests two sets of teacher education reforms have emerged as a result of rising awareness of adolescent literacy in public schools. Meyer (1999) explains “one set focus[es] on the content of teacher education—what courses and topics should be included—and another set focus[es] on the structure—where and when should teacher education take place and who should manage it” (p. 459). In addressing the second set of teacher education reforms, pre-service teachers are often afforded the opportunity to gain valuable professional training in public school classrooms, as field experiences are increasingly seen as an integral piece in the training of pre-service teachers. And, though these initiatives have shown improvement in teacher education, there are concerns, specifically in the field of language arts, that new teachers are not successfully negotiating the void that exists between theory and practice that is evident in some public school settings. So, with an expanding definition of literacy, and the rising awareness of secondary students’ literacy practices, there is a concern that pre-service teachers may in fact be unprepared to negotiate the demands of the career they have chosen for themselves. This study sets out to examine this problem. In preparing for a career in public education, certain expectations are formed by the teacher candidate based on what he or she understands adolescents should be able to do. These expectations are formed from a variety of sources. This study utilizes narrative inquiry to investigate the experiences of pre-service undergraduate language arts teachers who are completing a series of arranged field experiences. This study uses the stories of the participants to examine how the expectations of undergraduate pre-service language arts teachers are formed in regards to the range of high school students’ literacies. The data collected in this study indicate that while each participant in the study is operating from a different life stage, each has developed her own understanding of literacy and has the ability to apply that understanding to improve her practice. The ways in which these individually unique understandings of literacy vary widely and are, by in large, based on the personal experiences of each participant. This narrative study utilizes narrative analysis to investigate the storied experiences of three pre-service language arts teachers, on traditional undergraduate, one nontraditional undergraduate, and one self proclaimed “semi-nontraditional” undergraduate. Throughout the inquiry period, the primary research participants completed a field experience at a public high school located in American Midwest. During this field experience, each primary participant assisted a classroom teacher and tutored high school students during a common study hall period. Data was collected from a variety of sources including: personal interviews, video taped observations, reflective journals, and field notes. The storied experiences provided by the primary participants and field data were then reconstructed into narratives that present a meaningful representation of each participant’s experience in the field. These narratives also served as a meaningful platform for discussion in the final chapter of the report. The results of the study indicate that the participants base their expectations of high school students’ literacies on their own personal experiences. Throughout the inquiry period, each participant recalled their own experiences as a high school student when referencing literacy practices of the high school students under their direction. The narratives further illustrate noticeable differences in the understandings of literacy between the traditional and non-traditional participants. Where as the traditional undergraduates in the study were more reflective in their assessment of high school students’ literacies, the non-traditional undergraduate was more active in meeting the needs of the students she tutored and assisted during the field experience. In addition to providing answers to the primary and secondary research questions that investigate the participants’ developing expectations in terms of high school students’ literacies, the data also present themes that contribute to a better understanding of how the three pre-service language arts teachers negotiate the challenges that come with the major life transition of entering the professional workforce as a schoolteacher. While all three participants represent three different populations of undergraduate college students (i.e.: traditional, “semi-nontraditional”, and nontraditional), common themes of fear and uncertainty are present in each participant’s narrative. While these results are reminiscent of Fuller’s (1969) findings, it is important to understand that these feelings of fear and uncertainty are still present after forty years of advancements in teacher education. Which leads to further examination of the experiences these three participants have shared about the training they have received. Additionally, because each participant’s life experiences vary greatly from the other participants in the study, these feelings of fear and uncertainty are manifested differently for each participant. The findings of this study could have lasting implications to the fields of adolescent literacy and teacher education. While the definition of literacy is expanding to include not only academic literacy but social literacy practices that students experience beyond the classroom, the data in this study indicate that the participants who are close in age to the students the are preparing to teach seem open minded to use alternative texts that support academic literacies while encouraging students to explore their own interests. Additionally, each participant shared that she could benefit from more extensive field experiences where she could learn more about teaching as it is done in the field. And, as the data collected in this study indicate, more varied experiences tend to provide undergraduates with the necessary context to more successfully negotiate the demands of providing quality instruction.
Keywords: Pre-service teachers; Teacher education; Narrative inquiry; high school students' literacy’s; Education, Teacher Training (0530)